2020
DOI: 10.1021/acs.jced.0c00049
|View full text |Cite
|
Sign up to set email alerts
|

The Adsorption of Europium and Uranium on the Sodium Dodecyl Sulfate Modified Molybdenum Disulfide Composites

Abstract: With the wide use of nuclear energy, radioactive pollution has become a public environmental concern. In this study, the sodium dodecyl sulfate modified molybdenum disulfide (SDS/ MoS 2 ) was used to remove Eu(III) and U(VI). The experimental results demonstrated that the uptake of radionuclides on SDS/MoS 2 was dependent on solution pH. The maximum adsorption capacities of SDS/MoS 2 at pH 5.0 were 83.0 mg/g for Eu(III) and 98.4 mg/g for U(VI), respectively. The simultaneous adsorption experiment revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The interaction mechanism (i.e., electrostatic attraction, along with the hydroxyl and amidogen groups) of U(VI) on MoS 2 -based composites was demonstrated by DFT and XPS analysis. 2,243,247 Figure 9C showed the optimum configuration of adsorbed uranyl ion in the interlayer and/or on the surface of MoS 2 . The adsorption energies of UO 2 2+ adsorbed within the interlayer (−1.97 eV) of MoS 2 was much larger than that on the surface (−1.87 eV), suggesting strong interaction of UO 2 2+ within the interlayer.…”
Section: Removal Of Other Heavy Metalsmentioning
confidence: 99%
See 2 more Smart Citations
“…The interaction mechanism (i.e., electrostatic attraction, along with the hydroxyl and amidogen groups) of U(VI) on MoS 2 -based composites was demonstrated by DFT and XPS analysis. 2,243,247 Figure 9C showed the optimum configuration of adsorbed uranyl ion in the interlayer and/or on the surface of MoS 2 . The adsorption energies of UO 2 2+ adsorbed within the interlayer (−1.97 eV) of MoS 2 was much larger than that on the surface (−1.87 eV), suggesting strong interaction of UO 2 2+ within the interlayer.…”
Section: Removal Of Other Heavy Metalsmentioning
confidence: 99%
“…For instance, Gu et al reported that the flower-like polyvinyl pyrrolidine intercalated MoS 2 composites displayed the high removal performance toward U­(VI) (117.9 mg/g at pH 4.5, T = 298 K), compared to single MoS 2 (23.7 mg/g, Figure A) . Li et al reported that adsorption capacities of U­(VI) on MoS 2 (492.72 mg/g, pH 5.5, Figure B) were significantly higher that of the other MoS 2 -based composites such as sodium-dodecyl-sulfate-modified MoS 2 composites (98.4 mg/g), chitosan-modified MoS 2 (168.98 mg/g, at pH 5.0), respectively, , a fungal hyphae-graphene-MoS 2 hybrid (275 mg/g), and poly­(diethyl­(4-vinylbefqnzyl)­phosphonate- co -maleic anhydride) (448.4 mg/g at pH 4.0) …”
Section: Environmental Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, methods have been proposed to treat uranium-containing wastewater, including photocatalytic reduction, chemical precipitation, evaporation and concentration, ion exchange, electrochemistry, membrane treatment and adsorption. [1][2][3][4] Among them, the adsorption method is considered to be one of the most effective methods because of its simple operation, environmental friendliness and high efficiency. 5,6 At present, various adsorbents including carbon materials, 7,8 MOFs, [9][10][11] LDH, [12][13][14][15][16] etc.…”
Section: Introductionmentioning
confidence: 99%
“…At 298 K and pH = 4.5, the adsorption capacity of uranium reached 117.9 mg g −1 , which was significantly better than the original MoS 2 (23.7 mg g −1 ). Wang et al 2 used Na 2 MoO 4 and CH 3 CSNH 2 as molybdenum and sulfur sources to obtain SDS/MoS 2 by the hydrothermal method, and the maximum adsorption capacity of uranium was 98.4 mg g −1 at pH = 5.0. Due to the long reaction time and complex process of preparing MoS 2 by the hydrothermal method, Cui et al 19 used MoO 3 and S as raw materials to synthesize flower-like molybdenum disulfide by the solidstate method with Ar gas protection.…”
Section: Introductionmentioning
confidence: 99%